Macroeconomic theory and stabilization policy - Stevenson, A; Muscatelli, V; Gregory, M (Barnes and Noble, 1988)
A textbook for graduate and advanced undergraduate students outlining the main debates and issues in modern macroeconomics as they relate to questions of macroeconomic policy. Presumes a knowledge and grasp of intermediate macroeconomics. Concentrates on key issues rather than comprehensively covering macroeconomic theory and policy. Reviews the theory of aggregate demand and the classical versus Keynesian debate on underemployment equilibrium. Discusses aggregate supply in monetarist and new classical macroeconomics; the Keynesian perspective on aggregate supply and stabilization policies; money, financial markets, and aggregate demand; fiscal policy and aggregate demand; macroeconomic policy and the balance of payments; macroeconomic policy and the exchange rate; macroeconomic policy design; and international interdependence and policy coordination. Stevenson and Muscatelli are at the University of Glasgow. Gregory is at the University of Oxford. Bibliography; author and subject indexes.